Systemic Air Embolism Associated with Pleural Pigtail Chest Tube Insertion. (17th August 2016) - Alkhankan, Emad; Nusair, Ahmad; Mazagri, Rida; Al-Ourani, Mohammed
Abstract : Pleural pigtail catheter placement is associated with many complications including pneumothorax, hemorrhage, and chest pain. Air embolism is a known but rare complication of pleural pigtail catheter insertion and has a high risk of occurrence with positive pressure ventilation. In this case report, we present a 50-year-old male with bilateral pneumonia who developed a pneumothorax while on mechanical ventilation with continuous positive airway pressure mode. During the placement of the pleural pigtail catheter to correct the pneumothorax, the patient developed a sudden left sided body weakness and became unresponsive. An air embolism was identified in the right main cerebral artery, which was fatal.